Allelopathic Effect of Jatropha curcas on Selected Intercropping Plants (Green Chilli and Sesame) - N. Vijayakumar, S. Rejila* and (Journal of Phytology, 2011)
The aqueous leaf extracts of Jatropha curcas showed inhibitory effects on seed germination, shoot length and root length in Capsicum annum L.(green chilli).The inhibitory effect of the crop plant is directly proportional to the increasing concentration (5%, 10%, 15%, 20%) of aqueous leaf extracts of Jatropha curcas. The Jatropha curcas leaf extract showed stimulatory effects on seed germination and shoot length in Sesamum indicum L. (sesame). The stimulatory effect is directly proportional to the increasing concentration (5%, 10%, 15%, 20%), but the root growth was inhibited in all treatment when compared with the control. The result of bioassay studies revealed that the inhibitory and stimulatory effect may be due to the presence of water soluble allelochemicals like phenols and tannins etc.